Mapping patterns of support for privatization in the mass public: the case of Michigan - Thompson, Lyke; Elling, Richard C. (2000)
This article examines public attitudes about using for profit firms or nonprofit organizations to deliver public services in Michigan. Using survey data, it shows how the public reacts to the privatization of various state and local government services. It then considers some dimensions of attitudes toward privatization. Finally, it estimates models that predict support for privatization based upon a range of characteristics of respondents to our survey. - Reproduced
Keywords: Public administration; Privatization